Sosialisasi Persiapan Menghadapi Menarche dan Pencegahan Dismenorhea di SDN Purworejo 3 - Cintika Yorinda Sebtalesy; Dian Anisia Widyaningrum2 (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
School children are children who are at school age between 6-12 years. At this age, a healthy child will experience normal and reasonable growth and development, which is according to the standard of physical growth of children in general and has the ability according to the standard of ability of his age. During this time, children will experience a lot of development and growth in finding their identity and identity. Various psychological, physical (puberty) and social environmental changes will occur. Community service activities were carried out in February 2020. The activity was attended by 20 grade I students at SDN 03 Purworejo. The implementation of community service activities used is the dissemination of reproductive health as a preparation for facing menarche. The method used is the lecture method, question and answer method and games / quizzes. The result of this community service activity is the awareness of students to participate in socialization activities regarding reproductive health in preparation for facing menarche. Some of the supporting factors for these activities include: 1. The participants have a great willingness to get information and knowledge about socialization regarding reproductive health in preparation for facing menarche, 2. This health education activity is strongly supported by the school, both directly and indirectly participating actively in the implementation of health education regarding the dissemination of reproductive health in preparation for menarche. Constraints faced in the implementation of this health education are limitations in supporting facilities for making presentations including no image/slide display from the LCD projector due to time constraints and conditions. , and community service outcomes and implications.